Impact Of Maternal Education On Birth Weight and Gestational Age In West Java: A 2022 Study - Aprilia Kadi, Fiva; Pratiwi, Indah Anindya; Rakhmilla, Lulu Eva (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Infant development is greatly influenced by maternal health. Maternal factors such as level of education and age impact self-care during pregnancy, resulting in heterogeneity of birth weight and gestational age. Objective: This study analyzes the association between maternal level of education and age with birth weight and gestational age. Methods: A cross-sectional study with simple random sampling was performed by using medical records at Dr. Hasan Sadikin General Hospital Bandung from 1st January to 31st December 2019. Subjects were mothers who delivered single live-born and infants without congenital anomalies at Dr. Hasan Sadikin General Hospital Bandung. Data analysis represents the proportion between groups and the Mann-Whitney test (p<0.05) to observe the association between variables. Results: A total of 1574 birth data encounter the criteria in this study. Types of delivery, abnormality of amnion fluid, IUGR, PROM, and pregnancy complications didn’t differ between high- and low-risk groups of mothers. High-risk maternal age (<20 and >35 years old) was associated with gestational age (preterm birth, c=36.59 weeks; p=0.036). Maternal level of education wasn’t associated with gestational age and birth weight, also maternal age wasn’t associated with birth weight (p>0.05). Conclusion: High-risk maternal age (<20 and >35 years old) was associated with gestational age (preterm birth), however, a low level of education (no education, elementary school, and junior high school) wasn't shown to be related. Birth weight wasn't affected by maternal age and level of education. Further studies that account for socioeconomic aspect in regards of education level and birth weight and gestational age are necessary.